NCS-1 Deficiency Is Associated With Obesity and Diabetes Type 2 in Mice - Ratai, Olga; Hermainski, Joanna; Ravichandran, Keerthana; Pongs, Olaf (Frontiers in Molecular Neuroscience, 2019)
Neuronal calcium sensor-1 (NCS-1) knockout (KO) in mice (NCS-1−/− mice) evokes behavioral phenotypes ranging from learning deficits to avolition and depressive-like behaviors. Here, we showed that with the onset of adulthood NCS-1−/− mice gain considerable weight. Adult NCS-1−/− mice are obese, especially when fed a high-fat diet (HFD), are hyperglycemic and hyperinsulinemic and thus develop a diabetes type 2 phenotype. In comparison to wild type (WT) NCS-1−/− mice display a significant increase in adipose tissue mass. NCS-1−/− adipocytes produce insufficient serum concentrations of resistin and adiponectin. In contrast to WT littermates, adipocytes of NCS-1−/− mice are incapable of up-regulating insulin receptor (IR) concentration in response to HFD. Thus, HFD-fed NCS-1−/− mice exhibit in comparison to WT littermates a significantly reduced IR expression, which may explain the pronounced insulin resistance observed especially with HFD-fed NCS-1−/− mice. We observed a direct correlation between NCS-1 and IR concentrations in the adipocyte membrane and that NCS-1 can be co-immunoprecipitated with IR indicating a direct interplay between NCS-1 and IR. We propose that NCS-1 plays an important role in adipocyte function and that NCS-1 deficiency gives rise to obesity and diabetes type 2 in adult mice. Given the association of altered NCS-1 expression with behaviorial abnormalities, NCS-1−/− mice may offer an interesting perspective for studying in a mouse model a potential genetic link between some psychiatric disorders and the risk of being obese.